Clozapine: an effective treatment for seriously violent and psychopathic men with antisocial personality disorder in a UK high-security hospital. (3rd April 2014) - Brown, Darcy; Larkin, Fintan; Sengupta, Samrat; Romero-Ureclay, Jose L.; Ross, Callum C.; Gupta, Nitin; Vinestock, Morris; Das, Mrigendra
<x content-type="archive" xml:space="preserve">Abstract</x> Objective A number of studies have demonstrated the anti-aggressive properties of clozapine in schizophrenia and its positive effect in borderline personality disorder. There is no published literature on the treatment of antisocial personality disorder (ASPD) with clozapine. We present a case series of 7 patients with primary ASPD and high psychopathic traits treated with clozapine, having a significant history of serious violence and currently detained in a UK based high-security hospital. Methods A retrospective review of case notes was carried out to formulate Clinical Global Impression (CGI) scores and record incidents of violence and aggression. Effect on specific symptom domains (cognitive-perceptual, impulsive-behavioural dyscontrol, affective dysregulation) was also noted. Metabolic parameters and serum clozapine levels were also sampled. Results All 7 patients showed significant improvement on clozapine. It was shown to benefit all symptom domains, especially impulsive behavioral dyscontrol and anger. The number of violent incidents committed by 6 of the 7 patients reduced significantly, and all patients' risk of violence reduced. Clozapine serum levels for 6 of the 7 patients were in the range 150–350 ng/mL. Conclusion Clozapine is of benefit in reducing the clinical severity of ASPD. It improved all symptom domains, especially impulsive-behavioral dyscontrol and anger, and reduced levels of aggression and violence, especially at lower doses (serum levels <350 ng/m). To our knowledge, this is the first account of clozapine treatment in patients with ASPD and high psychopathy.